FLUXO: A Simple Service Compiler - Kiciman, Emre; Livshits, Ben; Musuvathi, Madan (12th Workshop on Hot Topics in Operating Systems, 2009)
In this paper, we propose FLUXO, a system that separates an Internet service’s logical functionality from the architectural decisions made to support performance, scalability, and reliability. FLUXO achieves this separation through three mechanisms: 1) a coarse-grained dataflow-based programming model; 2) detailed runtime request tracing to capture workload distributions, performance behavior, and resource requirements; and 3) a set of analysis techniques that determine how to apply simple, parameterized dataflow transformations to optimize the service architecture for performance, scalability, and reliability. In this paper, we describe our vision for how to make Internet services easier to construct, and show how a variety of Internet service performance optimizations may be expressed as transformations applied to FLUXO programs.